Augmented Reality, Customer Experience, and Repurchase Intention in the Cosmetic Products: Exploring the Mediating Role of Customer Satisfaction - Zahra Fakhiratunisa; Fadia Stevani; Siska Ernawati Fatimah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study investigates the mediating role of customer satisfaction (CS) in the relationship between augmented reality (AR), customer experience (CE), and repurchase intention (RI).Method: Data were collected from 399 Gen Z cosmetic consumers in Cirebon City through Likert-scale questionnaires. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used for analysis.Result: This study revealed that all hypotheses were supported. It found that AR positively influences CS, CE significantly impacts CS, and both AR and CE directly affect RI. Additionally, CS was shown to mediate the effects of both AR and CE on RI.Practical Implications for Economic Growth and Development: The findings offer valuable insights for the cosmetics and digital marketing sectors. Integrating AR features can enhance shopping experiences, reduce product-related uncertainty, and increase consumer confidence. Improved customer experience leads to higher satisfaction and loyalty, driving repeat purchases. These outcomes can help businesses lower customer acquisition costs, foster innovation in digital technologies, and strengthen market competitiveness—contributing to job creation and broader economic development in both retail and tech industries.Originality/Value: This study contributes a novel perspective by focusing on Gen Z and cosmetic products. This study also integrates AR and customer experience within a unified research model.